Hubungan Pengetahuan dengan Tingkat Kecemasan Remaja Putri Menghadapi Menarche di SMP Negeri 13 Kota Jambi - Fatihatul Hayati; Gustina Gustina (Universitas Baiturrahim, 2020)
Adolescence is a transitional period involving physical, emotional, and social development experienced by young women as a process of preparation for entering adulthood. In general, physical changes tend to be more dominating. Young women and menstruation have a very close relationship because menstruation is one of the important issues in young women. This study aims to determine the relationship between knowledge and anxiety levels of young women in the face of menarche. Subjects in this study were all students of SMP Negeri 13 Jambi City with a sample of 40 people. The sampling technique is proportional random sampling. Teenage anxiety levels were measured using the Hamilton Anxiety Rating Scale (HARS) questionnaire. There is a significant relationship between knowledge and anxiety levels of young women in the face of the first menstruation (menarche). It is hoped that there will be efforts to increase adolescent knowledge about reproductive health, especially menstrual preparation in the form of school programs in collaboration with local health centers.